Empirical study of Javanese leadership style in Surakarta, Indonesia - Suyono, Joko (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
This research aimed at testing empirically the Hastabrata Leadership as the leadership that was based on the local wisdom of the Javanese values. The research was conducted utilizing the survey method in which the main tool for collecting the data was the questionnaire. The research design was cross-sectional, that is, the research was carried out in the certain point of time in Sukoharjo and Sragen Disctricts. As many as 138 Village chiefs were chosen as the research samples using Cluster Sampling technique.  Data analysis was conducted using the Partial Least Square. The result showed that the dominant dimensions of the Hastabrata Leadership in Sukoharjo district happened to be different from those in Sragen district. The dominant dimensions in Sukoharjo district were the earth, the sun, the moon and the stars. While the dominant dimensions in Sragen district were the wind, the ocean, the fire, and the clouds. The different dominant dimensions between those two districts could not be separated from the historical factors of the division of the kingdom into Surakarta and Yogyakarta.